Sistem Kode Roland Barthes dalam Cerpen Emak Karya Fakhrunnas M. A. Jabbar - Ramadhani, Ananda; Suryaman, Maman (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The purpose of this research is to describe reading codes or lexics through Roland Barthes' semiotic theory in the form of proaretic codes, hermeneutic codes, connotative codes, symbolic codes, and cultural codes in a short story entitled Emak by Fakhrunnas M. A. Jabbar. This research uses a qualitative descriptive method with Roland Barthes's semiotic approach. The source of the data in this research were lexias or code readings in the short story Emak by Fakhrunnas M. A. Jabbar. Data collection techniques used in this study are reading and note-taking techniques. Data analysis techniques in this research used descriptive techniques, in the form of interpretation, analysis and conclusion. The results of this research are that there are 4 action code data, 2 puzzle code data, 1 connotative code data, 1 symbolic code data, and 2 cultural code data